WORKING CAPITAL MANAGEMENT AS A MEANS OF ENGENDERING CUSTOMER LOYALTY IN A BUSINESS-TO-BUSINESS CONTEXT - Muhammad Mubarak Sa'ad; Umaru Mustapha Zubairu (LPPM of NAROTAMA UNIVERSITY, 2022)
Adopting the Expectancy Confirmation Theory as its theoretical framework, this paper argued that working capital management (WCM) practices could be repurposed by firms in a business to business context in order to develop viable strategies to engender loyalty among its customers thus improving its chances at achieving long-term organizational success. The WCM-CL Model was developed to guide businesses on how to utilize inventory management practices, accounts receivable policies and accounts payable policies to help establish a loyal customer base. Specifically, the Model posited that a business which always had inventory on hand and rewarded loyal customers with generous credit terms would incentivize customers to become repeat-purchasers of its products and services. Additionally, the Model also encouraged companies to pay their suppliers as quickly as possible so as to develop a strong reputation of being a diligent and reliable customer among businesses within its supply chain network. The Model further argued that this strong reputation would attract other businesses in the network to become repeat customers due to the confidence they would have that the business would treat them fairly.